2013
DOI: 10.1186/1471-2458-13-1222
|View full text |Cite
|
Sign up to set email alerts
|

Appropriate health-seeking behavior and associated factors among people who had cough for at least two weeks in northwest Ethiopia: a population-based cross-sectional study

Abstract: BackgroundTuberculosis remains the major debilitating public health problem in Ethiopia. However, studies to understand the patients’ perspectives on the illness and their health-seeking behavior have been few in the country. In this study, we seek to investigate the magnitude of appropriate health-seeking behavior and factors associated with tuberculosis among people who had cough for at least two weeks.MethodsA population-based cross-sectional study was conducted from July to October 2012 in Dabat, northwest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 15 publications
1
24
3
Order By: Relevance
“…TB case-finding strategies for RIF resistant TB cases in Ethiopia focus on previously treated TB patients and the following groups of patients (HIV positive persons, contacts of patients with MDR-TB cases, refugees, prisoners and persons aged less than 15 years) [1,14,21,22]. Therefore, the present study was designed to assess the prevalence and assess the risk factors for RIF resistant TB at Dubti general hospital, Afar, north Ethiopia.…”
Section: Introductionmentioning
confidence: 99%
“…TB case-finding strategies for RIF resistant TB cases in Ethiopia focus on previously treated TB patients and the following groups of patients (HIV positive persons, contacts of patients with MDR-TB cases, refugees, prisoners and persons aged less than 15 years) [1,14,21,22]. Therefore, the present study was designed to assess the prevalence and assess the risk factors for RIF resistant TB at Dubti general hospital, Afar, north Ethiopia.…”
Section: Introductionmentioning
confidence: 99%
“…Similar findings were reported in Nigeria (Biya et al, 2014). A lack of sufficient knowledge regarding tuberculosis was the main reason contributing to delay in patients seeking healthcare (Biya et al, 2014); scholars have recommended intensifying health education programs to improve HSB (Biya et al, 2014;Senbeto et al, 2013). The most important descriptive factor influencing HSB was found to be the characteristics of the healthcare service itself (Adegoke, 2010).…”
Section: Health Seeking Behavior Of Menmentioning
confidence: 56%
“…Healthcare providers have been reported to be more welcoming to women in comparison to men (Galdas et al, 2005;Gerald & Ogwuche, 2014). A population-based cross-sectional study in Ethiopia demonstrated that, in general, men with a cough for at least two weeks were reluctant to seek healthcare services (Senbeto, Tadesse, Tadesse, & Melesse, 2013). Similar findings were reported in Nigeria (Biya et al, 2014).…”
Section: Health Seeking Behavior Of Menmentioning
confidence: 63%
“…Based on the outcome of quality assessments, no studies were excluded; instead, the information was considered during data synthesis and interpretation. 129 [29], 201 [30], 226 [31] Presumptive TB cases Case-control 838 [32] Crosssectional 476 [33], 843 [34], 1006 [35] 663 [36], 763 [37] Mozambique People with TB Crosssectional 622 [38] Tanzania People with TB Crosssectional 639 [39] 206 [ bStudy quality was assessed using the Newcastle-Ottawa scale. Highest possible score for cross-sectional studies was 10 (5 for selection, 2 for comparability, and 3 for outcome).…”
Section: Study Characteristics and Quality Assessmentsmentioning
confidence: 99%